FORMATION OF SOCIAL EDUCATOR’S DIGITAL COMPETENCE AS A WAY TO PROFESSIONAL GROWTH - Vlasii, Olesia; Dudka, Olha; Ivanochko, Nadiia (Educological discourse, 2021)
In the article, the impact of digitalization of education on the transformation of the professional competence of a social educators is analyzed; the need of the formation of digital competence of social educators in the context of the widespread implementation of information and communication technologies in the educational process is substantiated; the state of using educational Internet resources in the professional activities of social educators is analyzed; the importance of improving the level of digital competence as a component of the professional competence of social educators is substantiated; the use of digital tools as a practical toolkit for social educators is proposed; a brief overview of digital tools that will be useful in the work of a social educator is provided; a training course "Using Internet resources in the work of a social educator" developed by authors is presented; the course consists of four modules in accordance with the main directions of the social educator’s activities, in particular, diagnostic, developmental, educational and preventive work; the course has a practical focus, for the implementation of practical tasks, adapted to the professional activity of a social educator, instructional and methodological materials are developed that make it possible to conduct the course both offline and online; the course is developed on the principles of accessibility, comprehensibility, professional orientation and motivation; to implement the developed course, it is recommended to use the Google Classroom platform, which makes it possible to combine traditional and innovative forms and methods of teaching, which is especially important in the context of the introduction of distance and blended learning; the results of approbation of the developed course, which was conducted for social educators of the Nadvirnyansky district of Ivano-Frankivsk region are presented; taking into account the results of approbation, the conclusion is given about the advisability of using the course for the professional growth of social educators, including for the formation of the readiness of a social educator for the implementation of digital tools into professional activities.